PENGEMBANGAN KUESIONER UNTUK MENGEVALUASI USABILITAS E-LEARNING - Amalia Kiswandari; Rini Dharmastiti; Andi Rahadiyan Wijaya (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2016)
Interface design of e-learning sometimes people see only as a choice, not the main point. But, the basic thing about interface is it the main tool that have function to give user direction about how is using e-learning because it covers all element in e-learning. Usability is the tool that can measure the effective interaction between user and interface to achieve specific purpose. Questionnaire is a tool that practical, efficient and the most using tool to evaluate the usability. But, there is not yet a specific questionnaire in Indonesia that can evaluate usability of e-learning in general.The purpose of this study is to develop a measuring tool which is questionnaire that can capture usability problems in e-learning, know the usability questions attributes that become themost influence on the evaluation of the usability case studies in e-learning, and evaluate the problem of usability in the case study with the questionnaires which have been developed. The object of this study is an e-learning developed by the University of Gadjah Mada, namely eLisa, Synthesis (Faculty of Economics and Business), Gamel (Faculty of Medicine), and Papyrus (Department of Electrical Engineering and Information Technology). A sample of 317 respondents.The results of this study are valid and reliable questionnaire, and obtained 14 usability dimensions with 56 variables question from factor analysis result. This questionnaire has the consistency and relevance with the problems that reflected in open-ended questions, covered views from the mean value of merit usability. The comparison of four e-learning is a consistent ratings between the average value of variable merit 56 questions on the contents of the variable 5 questions in the concluding section. The result of comparisons with other questionnaires showed that the questionnaire is more effective because it can cover 73.21% of the existing problems in a more specific eLisa and evaluate a problem of usability.This research can still be developed and refined from research object of e-learning are more general by a combination of respondents from several countries to prove the relationship of user characteristics in terms of preference, culture, and language affect the evaluation of each individual to the usabiltity of e-elarning.